RESPON PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) DI TANAH PASIRAN AKIBAT PEMBERIAN PUPUK UREA BERPELAPIS BIOCHAR - Supriyadi, Slamet; Erika, Siti; Rahman, Fahmi Arief (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Biochar is an organic soil amendment that can be used as a coating in the production of slow-release fertilizers. This study aimed to determine the growth and yield response of corn in sandy soil due to the application of biochar-coated urea fertilizer, exploring the novelty of using coatings derived from local agricultural waste (which has been understudied) and the effectiveness of fertilizer dosage. The experiment was arranged in a Non-Factorial Completely Randomized Design (CRD) with 6 treatments, which were: P0, P1, P2, P3, P4, dan P5. Data were analyzed using ANOVA at 5%, followed by Duncan’s Multiple Range Test (DMRT) at 5% to determine the best treatment. The results showed that biochar-coated urea significantly influenced plant height during the advanced growth phase (42-84 DAP) but not in the early phase (14-28 DAP). For leaf number, treatments had significant effects at 42, 70, and 84 DAP, with P0 consistently yielding the lowest values. Leaf area also increased significantly at 42-84 DAP, with P3 showing the highest trend. The generative phase (flowering and cob development) was significantly affected by treatments. Meanwhile, corn production under P5 matched the results of P1. Implicatively, corn cob biochar-coated urea has the potential to replace conventional urea with a 20% lower dosage without compromising productivity, thereby reducing production costs and environmental pollution risks due to N leaching. These findings highlight opportunities to utilize corn cob waste as an eco-friendly material in slow-release fertilizer production.